Social media-driven behavioral mechanisms for sustainable park governance: a analysis of visitation intentions - Chen, Rong; Huang, Qi-tang; Miao, Lv-lin; Lin, Zheng; Gao, Dong-dong (Frontiers in Psychology, 2025)
Social media has emerged as a critical driver of urban park visitation, reshaping public perceptions and behavioral patterns through information dissemination and emotional resonance. This study investigates how social media usage influences recreational visitors’ intentions to visit urban parks, integrating the Theory of Planned Behavior (TPB) and the Stimulus-Organism-Response (S-O-R) model. Data were collected via questionnaires distributed to 535 visitors across four mountain parks in Fuzhou, China. Structural equation modeling (SEM) and Bootstrap methods were employed to analyze the relationships between social media usage intensity, information quality, perceived attractiveness, perceived crowding risk, subjective norms, and visitation intention. Results demonstrated that social media usage intensity (β = 0.374, p < 0.001) and information quality (β = 0.175, p < 0.001) directly and significantly influenced visitation intention. Perceptual factors partially mediated these relationships: usage intensity indirectly enhanced behavioral intention by increasing perceived attractiveness and strengthening subjective norms, while information quality optimized decision-making by reducing perceived crowding risk. The findings highlight the dual pathways of rational cognition and emotional drive in shaping visitor behavior, underscoring the importance of balancing ecological protection and visitor experience in smart park management. This framework provides data-driven insights for sustainable park governance.